MICROBIOLOGICAL PROFILE AND ANTIMICROBIAL RESISTANCE AMONG DIABETIC FOOT INFECTIONS: A CROSS-SECTIONAL STUDY FROM PALESTINE - Arjan, Amanee Soleman (An-Najah National University, 2025)
Abstract Background: Diabetic foot ulcers are serious complications that can increase morbidity and mortality among diabetic patients. Little is known about the different strains of bacteria that can be isolated from patients with diabetic foot ulcers who receive care in governmental hospitals in the north of the West Bank of Palestine. This study was conducted to evaluate the microbiological characteristics and bacterial resistance patterns of patients admitted to one of the main referral governmental hospitals in the north of the West Bank of Palestine. Methods: The study was conducted using a retrospective cross-sectional design. The study was conducted at Rafidia Surgical Hospital, which is one of the main referral governmental hospitals in the north of the West Bank of Palestine. The data were collected from patient records, laboratory reports, and sensitivity/resistance test findings. All referred patients to the hospital during January 2022 to December 2022 were included in the study. Results: In this study, files for 118 patients with diabetic foot infections who had culture results were identified, reviewed, and analyzed. Of these patients, 53 (44.9%) were admitted to the hospital for a heel pressure ulcer, and 46 (39.0%) were admitted for an infected toe. Of the 118 patients admitted, 4 cultures showed no growth, and 114 showed bacterial growth. Of the isolates, 67 (58.8%) were Gram-negative bacteria and 47 (41.2%) were Gram-positive bacteria. The detailed culture results are shown in Table 3. Of the 47 Gram-positive isolates, 1 (2.1%) was ESBL, and 18 (38.3%) were MRSA. None (0.0%) of the isolated Gram-positive strains were MDR. Of the 6 Enterococcus spp., 1 (16.7%) was ESBL. Of the 18 isolated Staphylococcus aureus, 11 (61.1%) were MRSA. On the other hand, 23 (31.3%) of the isolated Gram-negative bacteria were ESBL, and 7 (10.4%) were MDR. Of the 16 isolated Escherichia coli, 11 (68.8%) were ESBL. All 8 (100%) isolated Klebsiella pneumoniae were ESBL. Similarly, all 4 (100.0%) isolated Acinetobacter baumannii and both (100.0%) isolated Citrobacter spp. were MDR. Additionally, 1 (20.0%) of the 5 isolated Morganella morganii was ESBL, and 1 (20.0%) was MDR. Of the 2 isolated Enterobacter cloacae, 1 (50.0%) was ESBL. Among the Gram-negative isolates, 9 (13.4%) were CRE. Of the patients, 74 (62.7%) had moderately sized ulcers, and 31 (26.3%) had severely sized ulcers. The majority of the patients had osteomyelitis (62.7%) and gangrene (74.6%). Initially, the vast majority of patients (97.5%) received debridement. Of the patients, 41 (34.7%) received minor amputations, and 31 (26.3%) received major amputations. Patients who had neuropathy, were previously hospitalized in the last 90 days, had heart failure, hyperlipidemia, chronic kidney disease, malignancy, abnormally low HDL, osteomyelitis, gangrene, major amputations, and those who died had significantly higher rates of moderately and severely sized ulcers. Patients with low income, neuropathy, heart failure, chronic kidney disease, malignancy, osteomyelitis, gangrene, major amputation, and larger-sized ulcers were more likely to die. Conclusions: The epidemiology, microbiology, and clinical outcomes of diabetic foot infections in patients admitted to one of the main referral centers in Palestine were described. The findings showed that Gram-negative bacteria were the predominant pathogens isolated. A considerable proportion of the isolated bacteria was shown to be resistant to many antibiotics. The findings also showed that MRSA was prevalent among the Gram-positive isolates. This indicates that treating some diabetic foot infections could be highly challenging. The findings of this study showed that poor glycemic control, the presence of other diabetes-related complications, and the presence of other comorbidities correlated with disease severity and adverse outcomes. Decision-makers and healthcare providers should develop and implement antimicrobial stewardship programs and evidence-based treatment guidelines to optimize the outcomes of patients with diabetic foot infections.
الملامح الميكروبيولوجية ومقاومة مضادات الميكروبات بين التهابات القدم السكرية: دراسة مقطعية من فلسطين